2010
DOI: 10.1088/0031-8949/82/03/035801
|View full text |Cite
|
Sign up to set email alerts
|

Controlled structural and optical properties of ZnO nano-particles

Abstract: In this work, we have analyzed two synthesis procedures through experimental characterizations, where one provides a main temperature region for the control of the shape and size of ZnO nano-particles in comparison to the other. We have found that the complexing agent has a significant role in showing such a control region. This effect might also improve the fabrication and properties of other interesting and applicable nano-structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The values of surface to volume ratio is small, it means that the particles are completely spherical in shape. Similar results are reported in literature [17]. The surface area to volume ratio is large due to the small particle and the surface effect described for (Zn, Mn)-O pairs at the surface changing the Zn 1-x Mn x O nanoparticles of average crystallite size.…”
Section: Surface Area To Volume Ratiosupporting
confidence: 90%
“…The values of surface to volume ratio is small, it means that the particles are completely spherical in shape. Similar results are reported in literature [17]. The surface area to volume ratio is large due to the small particle and the surface effect described for (Zn, Mn)-O pairs at the surface changing the Zn 1-x Mn x O nanoparticles of average crystallite size.…”
Section: Surface Area To Volume Ratiosupporting
confidence: 90%
“…The calculated values of the S/V ratio are very small which means that the Zn 1-x Mn x O NPs are spherical in shape. Similar results have been reported in the literature (Kazemi et al, 2010).…”
Section: Xrd Structural Analysissupporting
confidence: 93%
“…At 500 ℃ annealing temperature, Yang et al [10] have observed good emission properties with fewer defects. Kazemi et al [11] have investigated the significant role of complexing agents on the structural and optical properties of ZnO nanoparticles with annealing treatment. However, the systematic study of the influence of annealing treatment on the structural and optical properties of ZnO nanoparticles with citric acid and polyvinyl alcohol as chelating agents has few reports.…”
Section: Introductionmentioning
confidence: 99%